2015
DOI: 10.1002/hep.27866
|View full text |Cite
|
Sign up to set email alerts
|

The (II)logic of iron reduction therapy for steatohepatitis

Abstract: A tool in the technique of logic that dates back to Aristotle is the use of a syllogism to prove an arguable point. In the context of iron reduction for steatohepatitis, it could unfold as follows:Major premise: An elevated serum ferritin can be associated with liver iron overload.Minor premise: Steatohepatitis is often associated with an elevated serum ferritin.Conclusion: Steatohepatitis can be associated with liver iron overload.The strength of the conclusion depends on the power or accuracy of the major an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Overall, although there are promising results from small studies, venesection cannot currently be recommended as a suitable therapy for the majority of patients with NAFLD[ 94 ]. However, whether there are sub-groups of non-hemochromatotic NAFLD patients with increased iron that would benefit from venesection, remains to be determined by further studies.…”
Section: Clinical Trials Of Iron Reduction Therapymentioning
confidence: 99%
“…Overall, although there are promising results from small studies, venesection cannot currently be recommended as a suitable therapy for the majority of patients with NAFLD[ 94 ]. However, whether there are sub-groups of non-hemochromatotic NAFLD patients with increased iron that would benefit from venesection, remains to be determined by further studies.…”
Section: Clinical Trials Of Iron Reduction Therapymentioning
confidence: 99%
“…[41] Thus, iron concentration in the liver might be lower than expected for a given serum ferritin level. [42] Adams et al . [17] reported that the mean ferritin level for a treatment group was 225 μg/L, which is within the reference range, and the hepatic iron concentration of this group was 23 μmol/g, which is in the mid-normal range as measured by magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients may not display obvious benefit because, in fact, they had no hepatic iron overload. [42]…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of patients with hyperferritinaemia do not present iron overload in the liver [28,29]. However, it is important to recognize which of them have iron overload in order to be treated by phlebotomy [19,[30][31][32][33]. This treatment does not offer any benefit to patients without iron overload and, moreover, it can generate some complications [19,34].…”
Section: Patients With Hyperferritinaemiamentioning
confidence: 99%